TELAAH PERBANDINGAN KURIKULUM 2013 DAN KMA 183-184 TAHUN 2019 DALAM PEMBELAJARAN BAHASA ARAB DI MADRASAH TSANAWIYAH - Lazuardi, Fajar; Tamami, Keysa; Ridho, Ubaid; Maswani, Maswani (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to analyze the conceptual and implementive differences between the 2013 Curriculum and the 2019 Curriculum (KMA No. 183-184 of 2019) in Arabic language learning at the Madrasah Tsanawiyah level. Using a qualitative research method based on literature study, this study examines the philosophical, sociological, psychopedagogical foundations, and characteristics of the two curriculums as listed in various official documents and scientific literature. The results of the study show that the 2013 Curriculum emphasizes national standardization through the structure of Core Competencies (KI) and Basic Competencies (KD) which are standard and centralized, so that Arabic language learning tends to be oriented to structural and theoretical aspects. On the contrary, KMA 183-184 of 2019 presents a new paradigm through Learning Outcomes (CP) and Learning Objectives (TP) that are more flexible, contextual, and oriented towards communicative competence and religious moderation. The 2019 curriculum also provides more space for the use of technology, strengthening local culture, and teacher autonomy in designing learning that is relevant to the needs of students and the challenges of the Industrial Revolution 4.0 era. Thus, it can be concluded that KMA 2019 offers a more adaptive, holistic, and functional approach to learning Arabic, while responding to global demands and the development of science and technology.